A preclinical overview of emerging therapeutic targets for glomerular diseases. (3rd July 2019) - Cassis, Paola; Zoja, Carlamaria; Perico, Luca; Remuzzi, Giuseppe
ABSTRACT: Introduction : Animal models have provided significant insights into the mechanisms responsible for the development of glomerular lesions and proteinuria; they have also helped to identify molecules that control the podocyte function as suitable target-specific therapeutics. Areas covered : We discuss putative therapeutic targets for proteinuric glomerular diseases. An exhaustive search for eligible studies was performed in PubMed/MEDLINE. Most of the selected reports were published in the last decade, but we did not exclude older relevant milestone publications. We consider the molecules that regulate podocyte cytoskeletal dynamics and the transcription factors that regulate the expression of slit-diaphragm proteins. There is a focus on SGLT2 and sirtuins which have recently emerged as mediators of podocyte injury and repair. We also examine paracrine signallings involved in the cross-talk of injured podocytes with the neighbouring glomerular endothelial cells and parietal epithelial cells. Expert opinion : There is a need to discover novel therapeutic moleecules with renoprotective effects for those patients with glomerular diseases who do not respond completely to standard therapy. Emerging strategies targeting components of the podocyte cytoskeleton or signallings that regulate cellular communication within the glomerulus are promising avenues for treating glomerular diseases.